Fluorescent BODIPY dyes as ligands for major steroidogenic proteins: in silico evaluation - Horetski, Matvey S.; Faletrov, Yaroslav V.; Rudaya, Elena V.; Shkumatov, Vladimir M. (Journal of the Belarusian State University. Chemistry, 2018)
In silico docking simulations of interactions between BODIPY-based fluorescent compounds and mammalian proteins, responsible for steroidogenesis, namely, cytochromes P450: CYP11A1, CYP17A1, CYP19A1, CYP7A1 and STARD1 transport protein, have been performed. Experimental results show a high affinity of some tested compounds to the active centers of the selected proteins (binding energies range of – 6.7 to –12.4 kcal/mol), indicating possible impact of BODIPY fluorescent tags into whole labeled molecules affinity towards the selected proteins and perspectives of the experimental testing of the predicted interactions. For the last purpose different BODIPY dyes were obtained using validated methodologies and characterized using spectrofluorimetry. A strategy of quantum chemical calculation, allowing us to predict the absorption spectra of the compounds under consideration, has been also developed. Our results demonstrate suitability of the calculations used for estimation of physical and biological properties of BODIPY-based compounds as a part of rational design of novel biological probes. Synthesized dyes have a potential as fluorescent probes for the biomedical studies.
Keywords: BODIPY; fluorescence; cytochrome P450; STARD1; docking; quantum chemical calculations